3-(4-Bromophenylsulfonyl)-8-methyl-1,3-diazaspiro[4.5]decane-2,4-dione - Kashif, M. Kalim (International Union of Crystallography, 2009)
The crystal structure of the title compound, C(15)H(17)BrN(2)O(4)S, is stabilized by intermolecular N—H⋯O hydrogen bonds which link the molecules into centrosymmetric dimers. The dihedral angle subtended by the 4-bromophenyl group with the mean plane passing through the hydantoin unit is 83.29 (5)°. The cyclohexyl group adopts an ideal chair conformation with the methyl group in an equatorial position.